Polishing composition, polishing method and method for manufacturing semiconductor substrate
The polishing composition, featuring abrasive grains with positive zeta potential, organic acid, nonionic surfactant, and hydrogen peroxide, addresses the challenge of controlling polishing selectivity by enhancing the polishing speed of certain films and suppressing others, thereby improving the overall polishing efficiency.
Patent Information
- Application Number
- JP2023169675
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
There is a need for a polishing composition that can control the polishing selectivity of materials containing two or more different film species, enhancing the polishing speed of certain films while suppressing others.
A polishing composition comprising abrasive grains with a positive zeta potential, an organic acid, a nonionic surfactant as an abrasive inhibitor, and hydrogen peroxide as an oxidizing agent, with a pH range of 2 to 4, is developed to achieve controlled polishing selectivity.
The composition effectively increases the polishing speed of specific film types, such as titanium nitride, while suppressing the polishing speed of other types, such as silicon oxide, thereby enhancing the polishing selectivity.
Smart Images

Figure 2025059532000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a polishing composition, a polishing method, and a method for producing a semiconductor substrate. [Background technology]
[0002] In recent years, with the trend toward multi-layer wiring on the surface of semiconductor substrates, a so-called chemical mechanical polishing (CMP) technique is used to polish and flatten semiconductor substrates when manufacturing devices. CMP is a method for flattening the surface of an object to be polished (object to be polished) such as a semiconductor substrate by using a polishing composition (slurry) containing abrasive grains such as silica, alumina, ceria, etc., an anticorrosive agent, a surfactant, etc., and the object to be polished (object to be polished) is a film containing silicon, polysilicon, silicon oxide (silicon oxide), silicon nitride, titanium nitride, titanium, tantalum nitride, tantalum, etc., wiring, plugs, etc. made of metals such as copper and tungsten, etc.
[0003] In particular, focusing on the polishing of titanium nitride, Patent Document 1 discloses that titanium films and titanium nitride films can be polished using a polishing composition containing an abrasive, at least one complexing agent selected from the group consisting of hydrogen peroxide, citric acid, lactic acid, tartaric acid, succinic acid, acetic acid, oxalic acid, and salts thereof, and a film-forming agent such as benzotriazole (BTA). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-021546 Summary of the Invention [Problem to be solved by the invention]
[0005] Recently, there has been a demand for controlling the polishing selectivity, that is, for an object to be polished that contains two or more different film types, by increasing the polishing rate of one film type and suppressing the polishing rate of another film type.
[0006] Therefore, an object of the present invention is to provide a polishing composition that can control the polishing selectivity, that is, improve the polishing rate of one film type and suppress the polishing rate of another film type, when the object to be polished contains two or more different film types. [Means for solving the problem]
[0007] In order to solve the above problems, the present inventors have conducted extensive research and have found that the above problems can be solved by a polishing composition comprising an abrasive grain, an acid, a polishing inhibitor, and an oxidizing agent, in which the abrasive grains have a positive zeta potential, the acid is an organic acid, the polishing inhibitor contains a nonionic surfactant, the oxidizing agent is hydrogen peroxide, and the pH is 2 or more and 4 or less, thereby completing the present invention. Effect of the Invention
[0008] According to the present invention, there is provided a polishing composition that can control the polishing selectivity, that is, improve the polishing rate of one film type and suppress the polishing rate of another film type, in a polishing object containing two or more different film types. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The following describes the embodiments of the present invention, but the present invention is not limited to the following embodiments and can be modified in various ways within the scope of the claims. The embodiments described in this specification can be combined in any way to form other embodiments. In this specification, unless otherwise specified, operations and measurements of physical properties are performed under the conditions of room temperature (20°C to 25°C) and relative humidity of 40% RH to 50% RH.
[0010] The present invention is a polishing composition comprising an abrasive grain, an acid, a polishing inhibitor, and an oxidizing agent, wherein the abrasive grain has a positive zeta potential, the acid is an organic acid, the polishing inhibitor comprises a nonionic surfactant, the oxidizing agent is hydrogen peroxide, and the pH is 2 to 4. With the polishing composition having such a constitution, the polishing rate of a certain film type can be improved and the polishing rate of a certain film type can be suppressed in a polishing object containing two or more different film types. That is, with the polishing composition having such a constitution, the polishing selectivity can be controlled in a polishing object containing two or more different film types. According to one embodiment, the inventors have estimated the mechanism by which such an effect is obtained by the present invention as follows. However, the following mechanism is an estimated mechanism taking the case where a polishing object containing a titanium nitride film and a silicon oxide film is used as an example, and the scope of the present invention is not limited by this.
[0011] In one embodiment of the present invention, the objective is to improve the polishing rate of the titanium nitride film and suppress the polishing rate of the silicon oxide film. Hydrogen peroxide, an oxidizing agent, is used to improve the polishing rate, but if the polishing rate of the silicon oxide film is improved, the polishing selectivity (hereinafter also simply referred to as "polishing selectivity of titanium nitride / silicon oxide"), which is expressed as the polishing rate of the titanium nitride film / the polishing rate of the silicon oxide film, decreases. It was also found that if the pH of the polishing composition is less than 2 or exceeds 4, the polishing rate of the silicon oxide film is improved and the polishing selectivity of titanium nitride / silicon oxide decreases. Therefore, a compound that does not affect the titanium nitride film but suppresses the polishing rate of the silicon oxide film was earnestly studied. As a result, a compound that selectively adsorbs to the silicon oxide film and inhibits contact with the abrasive grains by containing hydrogen peroxide, an oxidizing agent, in combination with an organic acid was found. That is, the present inventors have found that a nonionic surfactant can be a polishing suppressor for the silicon oxide film under certain conditions. The reason why the nonionic surfactant does not affect the titanium nitride film and selectively adsorbs to the silicon oxide film is unclear, but it is believed that the polarity of the nonionic surfactant is similar to that of the repeating unit of silicon oxide, and therefore the affinity is high. In the polishing composition of the present invention, under certain conditions, the nonionic surfactant selectively adsorbs onto the surface of the silicon oxide film to form a film that protects the surface of the silicon oxide film. This suppresses the contact between the silicon oxide film and the abrasive grains, suppressing the polishing speed of the silicon oxide film, and therefore it is believed that the polishing selectivity of titanium nitride / silicon oxide can be increased. As described above, the present inventor has found that the problem of providing a polishing composition with a high polishing selectivity of titanium nitride / silicon oxide can be solved by a polishing composition containing abrasive grains, an organic acid, a nonionic surfactant as a polishing suppressor, and hydrogen peroxide as an oxidizing agent, and having a pH of 2 to 4.
[0012] Therefore, in one embodiment of the present invention, the polishing composition of the present invention can polish a titanium nitride film at a higher polishing rate than the polishing rate of a silicon oxide film (i.e., the polishing selectivity, expressed as the polishing rate of the titanium nitride film / the polishing rate of the silicon oxide film, is high). Thus, in one embodiment, the polishing composition of the present invention can improve the polishing selectivity of titanium nitride / silicon oxide.
[0013] [Polished object] Examples of materials contained in the object to be polished with the polishing composition of the present invention include silicon oxide (SiO2), silicon nitride (SiN), silicon carbonitride (SiCN), polycrystalline silicon (polysilicon), non-crystalline silicon (amorphous silicon), metals, SiGe, Group 13 elements, etc. The object to be polished according to the present invention is preferably an object to be polished that contains two or more different film types.
[0014] Examples of films containing silicon oxide include, for example, TEOS (Tetraethyl Orthosilicate) type silicon oxide films (hereinafter, simply referred to as "TEOS films") produced using tetraethyl orthosilicate as a precursor, HDP (High Density Plasma) films, USG (Undoped Silicate Glass) films, PSG (Phosphorus Silicate Glass) films, BPSG (Boron-Phospho Silicate Glass) films, and RTO (Rapid Thermal Oxidation (CO) films and the like.
[0015] Examples of the metal-containing film include tungsten (W) film, titanium nitride (TiN) film, ruthenium (Ru) film, platinum (Pt) film, gold (Au) film, hafnium (Hf) film, cobalt (Co) film, nickel (Ni) film, copper (Cu) film, aluminum (Al) film, and tantalum (Ta) film. From the viewpoint of improving electrical conductivity, preferably, W film, TiN film, Ru film, Pt film, or Au film is used, particularly preferably, W film or TiN film is used, and most preferably, W film is used. In one embodiment, the polishing composition of the present invention can be used to suitably polish a polishing target containing a metal (e.g., tungsten).
[0016] The object to be polished according to the present invention may have a layer containing 40 mass% or more of a Group 13 element (hereinafter, simply referred to as a Group 13 element layer). Examples of Group 13 elements include boron (B), aluminum (Al), gallium (Ga), and indium (In). The Group 13 elements may be used alone or in combination of two or more.
[0017] The Group 13 element layer may contain elements other than the Group 13 elements. Examples of the other elements include silicon (Si), hydrogen (H), nitrogen (N), oxygen (O), carbon (C), phosphorus (P), germanium (Ge), etc. These other elements may be contained alone or in combination of two or more.
[0018] The lower limit of the amount of the Group 13 element contained in the Group 13 element layer is 40 mass% or more, preferably 45 mass% or more, and more preferably 50 mass% or more, based on the mass of the entire layer. The upper limit of the amount of the Group 13 element contained in the Group 13 element layer is preferably 100 mass% or less, more preferably 95 mass% or less, and even more preferably 90 mass% or less, based on the mass of the entire layer.
[0019] The object to be polished according to the present invention can control the polishing selectivity, that is, the polishing rate of one film type is improved and the polishing rate of another film type is suppressed, in an object to be polished that includes two or more different film types. The object to be polished according to the present invention preferably includes a silicon oxide film or a titanium nitride film. Therefore, the polishing composition of the present invention is preferably used for polishing an object to be polished that includes a silicon oxide film or a silicon nitride film.
[0020] In one embodiment, the object to be polished according to the present invention preferably contains an element of Group 13. Therefore, the polishing composition of the present invention is preferably used for polishing an object to be polished that contains an element of Group 13.
[0021] Furthermore, the shape of the object to be polished is not particularly limited. In one embodiment of the present invention, the polishing composition can be preferably applied to polishing an object to be polished having a flat surface, such as a plate-like or polyhedral shape.
[0022] [Abrasive grain] The polishing composition according to the present invention contains abrasive grains. The abrasive grains contained in the polishing composition according to the present invention have a positive zeta potential. The abrasive grains are preferably cation-modified silica (silica having a cationic group), more preferably cation-modified colloidal silica (colloidal silica having a cationic group). The abrasive grains may be used alone or in combination of two or more kinds. In addition, the abrasive grains may be commercially available products or synthetic products.
[0023] The method for producing colloidal silica includes a sodium silicate method and a sol-gel method, and colloidal silica produced by either method can be suitably used as the abrasive grain according to the present invention. However, from the viewpoint of reducing metal impurities, colloidal silica produced by the sol-gel method is preferred. Colloidal silica produced by the sol-gel method is preferred because it contains less metal impurities that are diffusible in semiconductors and less corrosive ions such as chloride ions. Colloidal silica can be produced by the sol-gel method using a conventionally known method, and specifically, colloidal silica can be obtained by hydrolysis and condensation reaction using a hydrolyzable silicon compound (e.g., alkoxysilane or its derivative) as a raw material.
[0024] Here, cation-modified means a state in which a cationic group (e.g., an amino group or a quaternary ammonium group) is bonded to the surface of silica (preferably colloidal silica). According to a preferred embodiment of the present invention, the cation-modified silica particles are amino-modified silica particles, more preferably amino-modified colloidal silica particles. According to such an embodiment, the above-mentioned effects can be further improved.
[0025] To cationically modify silica (colloidal silica), a silane coupling agent having a cationic group (e.g., an amino group or a quaternary ammonium group) is added to silica (colloidal silica) and reacted at a predetermined temperature for a predetermined time. In a preferred embodiment of the present invention, the cationically modified silica is obtained by fixing a silane coupling agent having an amino group or a silane coupling agent having a quaternary ammonium group to the surface of silica (more preferably colloidal silica).
[0026] In this case, the silane coupling agent used may be, for example, that described in JP-A-2005-162533.Specific examples of the silane coupling agent include N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, γ-aminopropyltriethoxysilane ((3-aminopropyl)triethoxysilane), γ-aminopropyltrimethoxysilane, γ-triethoxysilyl-N-(α,γ-dimethyl-butylidene)propylamine, N-phenyl-γ-aminopropyltrimethoxysilane, N-(vinylbenzyl)-β-aminoethyl-γ-aminopropyltriethoxysilane hydrochloride, octadecyldimethyl-(γ-trimethoxysilylpropyl)-ammonium chloride, and N-trimethoxysilylpropyl-N,N,N-trimethylammonium chloride. Among them, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, γ-aminopropyltriethoxysilane, and γ-aminopropyltrimethoxysilane are preferably used because of their good reactivity with colloidal silica. In the present invention, the silane coupling agent may be used alone or in combination of two or more kinds.
[0027] The silane coupling agent can be added to silica (colloidal silica) as is or after diluting with a hydrophilic organic solvent or pure water. By diluting with a hydrophilic organic solvent or pure water, the formation of aggregates can be suppressed. When the silane coupling agent is diluted with a hydrophilic organic solvent or pure water, the silane coupling agent is dissolved in the hydrophilic organic solvent or pure water. The hydrophilic organic solvent may be diluted with pure water or a hydrophilic organic solvent so that the concentration is preferably about 0.01 g to 1 g, more preferably about 0.1 g to 0.7 g, per 1 L of pure water. The hydrophilic organic solvent is not particularly limited, but examples thereof include lower alcohols such as methanol, ethanol, isopropanol, and butanol.
[0028] In addition, the amount of cationic groups introduced to the surface of silica (colloidal silica) can be adjusted by adjusting the amount of silane coupling agent added. The amount of silane coupling agent used is not particularly limited, but is preferably 0.1 mM (mmol / L) or more and 5 mM or less, more preferably 0.5 mM or more and 3 mM or less, relative to the reaction solution.
[0029] The treatment temperature when the silica (colloidal silica) is cationically modified with the silane coupling agent is not particularly limited, and may be from room temperature (e.g., 25°C) to a temperature about the boiling point of the dispersion medium in which the silica (colloidal silica) is dispersed, specifically, from 0°C to 100°C, and preferably from room temperature (e.g., 25°C) to 90°C.
[0030] The lower limit of the zeta potential of the abrasive grain in the polishing composition is preferably 5 mV or more, more preferably 10 mV or more, even more preferably 15 mV or more, particularly preferably 18 mV or more, and most preferably 20 mV or more.The upper limit of the zeta potential of the abrasive grain in the polishing composition is preferably 70 mV or less, more preferably 60 mV or less, even more preferably 50 mV or less, particularly preferably 40 mV or less, and most preferably 35 mV or less.That is, the zeta potential of the abrasive grain in the polishing composition is preferably 5 mV or more and 70 mV or less, more preferably 10 mV or more and 60 mV or less, even more preferably 15 mV or more and 50 mV or less, particularly preferably 18 mV or more and 40 mV or less, and most preferably 20 mV or more and 35 mV or less.
[0031] In an object to be polished that includes two or more different film types, the abrasive grains having the above-mentioned zeta potential can improve the polishing rate of one film type and suppress the polishing rate of another film type. According to one embodiment, the abrasive grains having the above-mentioned zeta potential can polish a titanium nitride film at a higher polishing rate, and the polishing rate of the titanium nitride film is higher than the polishing rate of the silicon oxide film (the polishing selectivity is higher).
[0032] The shape of the abrasive grains is not particularly limited, and may be spherical or non-spherical. Specific examples of non-spherical shapes include polygonal prisms such as triangular prisms and square prisms, cylinders, bales in which the center of a cylinder is bulged out more than the ends, donut shapes in which the center of a disk is penetrated, plates, so-called cocoons with a constriction in the center, so-called association-type spheres in which multiple particles are integrated, so-called confetti shapes with multiple protrusions on the surface, and rugby ball shapes, and various other shapes are not particularly limited.
[0033] The average primary particle diameter of the abrasive grains is preferably 1 nm or more, more preferably 3 nm or more, and even more preferably 5 nm or more. When the average primary particle diameter of the abrasive grains is within the above lower limit, the polishing speed of a certain film type can be improved and the polishing speed of another film type can be suppressed in a polishing object containing two or more different film types. According to one embodiment, as the average primary particle diameter of the abrasive grains increases, the polishing speed of the titanium nitride film increases. In addition, the average primary particle diameter of the abrasive grains is preferably 100 nm or less, more preferably 50 nm or less, and even more preferably 30 nm or less. When the average primary particle diameter of the abrasive grains is within the above upper limit, the polishing speed of a certain film type can be improved and the polishing speed of another film type can be suppressed in a polishing object containing two or more different film types. According to one embodiment, as the average primary particle diameter of the abrasive grains decreases, the polishing speed of the titanium nitride film becomes higher than the polishing speed of the silicon oxide film (the polishing selectivity becomes higher).
[0034] That is, the average primary particle size of the abrasive grains is preferably 1 nm or more and 100 nm or less, more preferably 3 nm or more and 50 nm or less, and even more preferably 5 nm or more and 30 nm or less. The average primary particle size of the abrasive grains can be calculated, for example, based on the specific surface area (SA) of the abrasive grains calculated by the BET method and the density of the abrasive grains. More specifically, the average primary particle size of the abrasive grains is a value measured by the method described in the Examples.
[0035] The average secondary particle diameter of the abrasive grains is preferably 15 nm or more, more preferably 20 nm or more, and even more preferably 25 nm or more. When the average secondary particle diameter of the abrasive grains is at the lower limit, the polishing speed of a certain film type can be improved and the polishing speed of another film type can be suppressed. According to one embodiment, as the average secondary particle diameter of the abrasive grains increases, the resistance during polishing decreases, and stable polishing of the titanium nitride film is possible. In addition, the average secondary particle diameter of the abrasive grains is preferably 200 nm or less, more preferably 150 nm or less, and even more preferably 100 nm or less. When the average secondary particle diameter of the abrasive grains is at the upper limit, the polishing speed of a certain film type can be improved and the polishing speed of another film type can be suppressed. According to one embodiment, as the average secondary particle diameter of the abrasive grains decreases, the surface area per unit mass of the abrasive grains increases, the frequency of contact with the object to be polished increases, and the polishing speed of the titanium nitride film is further improved. That is, the average secondary particle size of the abrasive grains is preferably 15 nm or more and 200 nm or less, more preferably 20 nm or more and 150 nm or less, and even more preferably 25 nm or more and 100 nm or less. The average secondary particle size of the abrasive grains can be measured, for example, by a dynamic light scattering method represented by a laser diffraction scattering method, and specifically, the value measured by the method described in the Examples is used.
[0036] The ratio of the average secondary particle diameter to the average primary particle diameter of the abrasive grains (average secondary particle diameter / average primary particle diameter, hereinafter also referred to as "average degree of association") is preferably more than 1.0, more preferably 1.1 or more, and even more preferably 1.2 or more. When the average degree of association of the abrasive grains is at the lower limit, the polishing speed of a certain film type can be improved and the polishing speed of another film type can be suppressed. According to one embodiment, as the average degree of association of the abrasive grains increases, the polishing speed of the titanium nitride film can be improved. In addition, the average degree of association of the abrasive grains is preferably 4 or less, more preferably 3.5 or less, and even more preferably 3 or less. When the average degree of association of the abrasive grains is at the upper limit, the polishing speed of a certain film type can be improved and the polishing speed of another film type can be suppressed. According to one embodiment, as the average degree of association of the abrasive grains decreases, the polishing speed of the titanium nitride film becomes higher than the polishing speed of the silicon oxide film (the polishing selectivity becomes higher). That is, the average degree of association of the abrasive grains is preferably more than 1.0 and not more than 4, more preferably 1.1 or more and 3.5 or less, and even more preferably 1.2 or more and 3 or less.
[0037] The average degree of association of abrasive grains is obtained by dividing the average secondary particle size of the abrasive grains by the average primary particle size of the abrasive grains.
[0038] The upper limit of the aspect ratio of the abrasive grains in the polishing composition is not particularly limited, but is preferably less than 2.0, more preferably 1.8 or less, and even more preferably 1.5 or less. In such a range, defects on the surface of the object to be polished can be further reduced. The aspect ratio is the average value obtained by taking the smallest rectangle that circumscribes the image of the abrasive grains using a scanning electron microscope, and dividing the length of the long side of the rectangle by the length of the short side of the same rectangle, and can be determined using general image analysis software. The lower limit of the aspect ratio of the abrasive grains in the polishing composition is not particularly limited, but is preferably 1.0 or more.
[0039] The size of the abrasive grains (average primary particle size, average secondary particle size, aspect ratio, etc.) can be appropriately controlled by selecting the manufacturing method of the abrasive grains, etc.
[0040] In this specification, the zeta potential of the abrasive grains is a value measured by the method described in the Examples. The zeta potential of the abrasive grains can be adjusted by the amount of cationic groups contained in the abrasive grains, the pH of the polishing composition, etc.
[0041] In the polishing composition according to the present invention, the abrasive grains may be used alone or in combination of two or more kinds. In addition, the abrasive grains to be used may be either commercially available products or synthetic products.
[0042] The content (concentration) of the abrasive grains in the polishing composition is not particularly limited, but is preferably 0.1 mass% or more, more preferably 0.2 mass% or more, even more preferably 0.5 mass% or more, and particularly preferably more than 0.5 mass% based on the total mass of the polishing composition. The upper limit of the content of the abrasive grains in the polishing composition is preferably 10 mass% or less, more preferably 5 mass% or less, even more preferably 4 mass% or less, and particularly preferably less than 4 mass% based on the total mass of the polishing composition. That is, the content of the abrasive grains is preferably 0.1 mass% or more and 10 mass% or less, more preferably 0.2 mass% or more and 5 mass% or less, even more preferably 0.5 mass% or more and 4 mass% or less, and particularly preferably more than 0.5 mass% and less than 4 mass% based on the total mass of the polishing composition. In one embodiment, the content (concentration) of the abrasive grains in the polishing composition is 0.01 mass% or more and 3.0 mass% or less.
[0043] If the content of the abrasive grains is within this range, the polishing speed of some film types can be improved, and the polishing speed of other film types can be suppressed. According to one embodiment, if the content of the abrasive grains is within this range, the titanium nitride film can be polished at a higher polishing speed, and the polishing speed of the titanium nitride film is higher than the polishing speed of the silicon oxide film (the polishing selectivity is higher). When the polishing composition contains two or more types of abrasive grains, the content of the abrasive grains refers to the total amount of these.
[0044] When cation-modified silica is used as abrasive grains in the polishing composition according to the present invention, other abrasive grains than cation-modified silica may be further included within the range that does not impair the effect of the present invention. Such other abrasive grains may be any of inorganic particles, organic particles, and organic-inorganic composite particles. Specific examples of inorganic particles include unmodified silica, particles made of metal oxides such as alumina, ceria, and titania, silicon nitride particles, silicon carbide particles, and boron nitride particles. Specific examples of organic particles include polymethylmethacrylate (PMMA) particles.
[0045] [Polishing inhibitor] The polishing composition according to the present invention contains a nonionic surfactant as a polishing suppressor. The nonionic surfactant has a function of suppressing the polishing rate of a certain film type (e.g., a silicon oxide film). In one embodiment, the nonionic surfactant has a function of suppressing the polishing rate of a silicon oxide film. Thus, according to one embodiment, the polishing suppressor is a silicon oxide polishing suppressor. The nonionic surfactant may be used alone or in combination of two or more kinds. In addition, the nonionic surfactant may be a commercially available product or a synthetic product.
[0046] Examples of the nonionic surfactant used in the polishing composition according to the present invention include alkyl betaines, alkyl amine oxides, polyoxyalkylene glycols, polyoxyalkylene alkyl ethers, sorbitan fatty acid esters, glycerin fatty acid esters, polyoxyalkylene fatty acid esters, polyoxyalkylene alkylamines, and alkyl alkanolamides. Among them, from the viewpoint of controlling the polishing selectivity in an object to be polished that includes two or more different film types (for example, from the viewpoint of improving the polishing selectivity of titanium nitride / silicon oxide), compounds having a polyoxyalkylene glycol structure such as polyoxyalkylene glycols and polyoxyalkylene alkyl ethers (hereinafter also referred to as "polyoxyalkylene glycol-based compounds") are preferred.
[0047] In a preferred embodiment, the polishing composition according to the present invention contains a compound having a polyoxyalkylene glycol structure as a nonionic surfactant. In a more preferred embodiment, the polishing composition according to the present invention contains a compound having one or more structures selected from the group consisting of a polyethylene glycol structure and a polypropylene glycol structure as a nonionic surfactant. In a further preferred embodiment, the polishing composition according to the present invention contains a compound having one or more structures selected from the group consisting of a polypropylene glycol structure as a nonionic surfactant. By using a polyoxyalkylene glycol compound as a nonionic surfactant, the effect of suppressing the polishing rate of the silicon oxide film is further exerted. The polyoxyalkylene glycol compound may be used alone or in combination of two or more kinds. In addition, the polyoxyalkylene glycol compound may be a commercially available product or a synthetic product.
[0048] Examples of the polyoxyalkylene glycol-based compound include an oxyalkylene homopolymer, an oxyalkylene copolymer, a polyoxyalkylene alkyl ether, etc. Thus, in one embodiment, the polishing composition according to the present invention contains one or more selected from the group consisting of polyethylene glycol, polypropylene glycol, polyethylene alkyl ether, and polypropylene ether.
[0049] The oxyalkylene homopolymer and oxyalkylene copolymer are not particularly limited, and examples thereof include polyethylene glycol, polypropylene glycol, polyethylene glycol-polypropylene glycol random copolymer, polyethylene glycol-polytetramethylene glycol random copolymer, polypropylene glycol-polytetramethylene glycol random copolymer, polyethylene glycol-polypropylene glycol-polytetramethylene glycol random copolymer, polyethylene glycol-polypropylene glycol block copolymer, polypropylene glycol-polyethylene glycol-polypropylene glycol triblock copolymer, polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer, etc. Among these, polyethylene glycol and polypropylene glycol are preferred, and polypropylene glycol is more preferred.
[0050] Examples of polyoxyalkylene alkyl ethers include polyoxyethylene monodecyl ether, polyoxyethylene monoundecyl ether, polyoxyethylene monododecyl ether (polyoxyethylene monolauryl ether), polyoxyethylene didodecyl ether (polyoxyethylene dilauryl ether), polyoxyethylene tetradecyl ether (polyoxyethylene myristyl ether), polyoxyethylene monotetradecyl ether (polyoxyethylene monomyristyl ether), polyoxyethylene monooleyl ether, and polyoxyethylene dioleyl ether.
[0051] In one embodiment, the polishing composition of the present invention contains one or more selected from the group consisting of polyethylene glycol, polypropylene glycol, polyethylene alkyl ether, and polypropylene ether.
[0052] The number average molecular weight (Mn) of the nonionic surfactant (preferably a polyoxyalkylene glycol compound) is preferably 100 or more, more preferably 150 or more, even more preferably 200 or more, particularly preferably 250 or more, and most preferably 300 or more. The weight average molecular weight (Mw) of the nonionic surfactant (preferably a polyoxyalkylene glycol compound) may be, for example, 2000 or less, preferably less than 1000, more preferably 900 or less, even more preferably 800 or less, particularly preferably 700 or less, and most preferably 600 or less. That is, the number average molecular weight (Mn) of the nonionic surfactant (preferably a polyoxyalkylene glycol compound) is preferably 100 or more and less than 1000, more preferably 150 or more and 900 or less, even more preferably 200 or more and 800 or less, particularly preferably 250 or more and 700 or less, and most preferably 300 or more and 600 or less. In one embodiment, the number average molecular weight (Mn) of the nonionic surfactant (preferably a polyoxyalkylene glycol-based compound) is 200 or more and less than 1,000. In one embodiment, the polishing inhibitor is polypropylene glycol having a number average molecular weight of 200 or more and less than 1,000.
[0053] In this specification, the number average molecular weight (Mn) of the nonionic surfactant can be measured by gel permeation chromatography (GPC) using polyethylene glycol as a standard substance. For example, it can be measured under the following conditions.
[0054] [Measurement of number average molecular weight (Mn) of nonionic surfactants] The number average molecular weight (Mn) of the nonionic surfactant was determined by gel permeation chromatography (GPC) using the number average molecular weight (converted into polyethylene glycol). The number average molecular weight was measured using the following apparatus and conditions: GPC equipment: Shimadzu Corporation Model: Prominence + ELSD detector (ELSD-LTII) Column: VP-ODS (Shimadzu Corporation) Mobile phase A: Methanol B: 1% acetic acid solution Flow rate: 1mL / min Detector: ELSD temp. 40℃, Gain 8, N2GAS 350kPa Oven temperature: 40℃ Injection volume: 40μL.
[0055] The content (concentration) of the nonionic surfactant (polyoxyalkylene glycol compound) in the polishing composition is not particularly limited, but is preferably 0.001% by mass or more, more preferably 0.005% by mass or more, even more preferably 0.01% by mass or more, particularly preferably 0.05% by mass or more, and most preferably 0.07% by mass or more, based on the total mass of the polishing composition. The content of the nonionic surfactant (polyoxyalkylene glycol compound) in the polishing composition is preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 2% by mass or less, particularly preferably 1% by mass or less, and most preferably 0.8% by mass or less, based on the total mass of the polishing composition. If the content of the nonionic surfactant (polyoxyalkylene glycol compound) is within such a range, the polishing selectivity can be controlled in a polishing object containing two or more different film types. According to one embodiment, when the content of the nonionic surfactant (polyoxyalkylene glycol compound) is within this range, the polishing rate of the silicon oxide film can be further suppressed, and the polishing rate of the titanium nitride film becomes higher than the polishing rate of the silicon oxide film (the polishing selectivity becomes higher).
[0056] That is, the content (concentration) of the nonionic surfactant (polyoxyalkylene glycol compound) in the polishing composition is preferably 0.001 mass% or more and 10 mass% or less, more preferably 0.005 mass% or more and 5 mass% or less, even more preferably 0.01 mass% or more and 2 mass% or less, particularly preferably 0.05 mass% or more and 1 mass% or less, and most preferably 0.07 mass% or more and 0.8 mass% or less, relative to the total mass of the polishing composition.
[0057] The polishing composition according to the present invention may contain other surfactants (hereinafter referred to as "other surfactants") other than the nonionic surfactant. The other surfactant may be a surfactant having at least one functional group selected from a cationic group and an anionic group in the molecule. The number average molecular weight (Mn) of the other surfactant is preferably 100 or more and 1000 or less. The other surfactant may be used alone or in combination of two or more. When the polishing composition according to the present invention contains other surfactants, the mass ratio of the nonionic surfactant to the other surfactant (nonionic surfactant: other surfactant) is preferably 80:20 to 99.99:0.01, more preferably 90:10 to 99.9:0.1.
[0058] [acid] The polishing composition according to the present invention contains an organic acid as an acid. The organic acid functions as a pH adjuster. The organic acid includes a carboxylic acid and a sulfur-containing organic acid.
[0059] Specific examples of carboxylic acids include formic acid, acetic acid, propionic acid, butyric acid, valeric acid, 2-methylbutyric acid, n-hexanoic acid, 3,3-dimethylbutyric acid, 2-ethylbutyric acid, 4-methylpentanoic acid, n-heptanoic acid, 2-methylhexanoic acid, n-octanoic acid, 2-ethylhexanoic acid, benzoic acid, glycolic acid, salicylic acid, glyceric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, maleic acid, phthalic acid, malic acid, tartaric acid, citric acid, and lactic acid. Specific examples of sulfur-containing organic acids include methanesulfonic acid, ethanesulfonic acid, 10-camphorsulfonic acid, and isethionic acid. These acids may be used alone or in combination of two or more.
[0060] The organic acid is preferably a sulfur-containing organic acid, more preferably an organic acid having a sulfonic acid group, and therefore is preferably methanesulfonic acid, ethanesulfonic acid, 10-camphorsulfonic acid, or isethionic acid, and more preferably 10-camphorsulfonic acid.
[0061] The content (concentration) of the organic acid in the polishing composition is not particularly limited, but is preferably 0.001 mass% or more, more preferably 0.005 mass% or more, based on the total mass of the polishing composition. The content of the organic acid in the polishing composition is preferably 10 mass% or less, more preferably 5 mass% or less, based on the total mass of the polishing composition. If the content of the acid is in this range, the polishing selectivity can be controlled in a polishing object containing two or more different film types. According to one embodiment, if the content of the acid is in this range, the titanium nitride film can be polished at a higher polishing rate, and the polishing rate of the titanium nitride film is higher than the polishing rate of the silicon oxide film (the polishing selectivity is higher).
[0062] In the polishing composition according to the present invention, the organic acid plays a role as a pH adjuster of the polishing composition, so that the amount of the organic acid added may be appropriately adjusted so that the pH of the polishing composition is, for example, 2 or more and 4 or less. For example, when 10-camphorsulfonic acid is used, the amount of the organic acid added is preferably 0.005% by mass or more and 1% by mass or less, more preferably 0.008% by mass or more and 0.500% by mass or less, and particularly preferably 0.010% by mass or more and 0.100% by mass or less, based on the total mass of the polishing composition. In one embodiment, the content of 10-camphorsulfonic acid is 0.01% by mass or more and 0.03% by mass or less, based on the total mass of the polishing composition.
[0063] [Oxidizing agent] The polishing composition according to the present invention contains an oxidizing agent. The oxidizing agent causes an oxidation reaction with the surface of the object to be polished during the polishing process, and can reduce the hardness of the surface and make the surface fragile. By using the oxidizing agent, the polishing selectivity can be controlled in the object to be polished that includes two or more different film types. According to one embodiment, the oxidizing agent can effectively improve the polishing speed of the object to be polished, such as a titanium nitride film.
[0064] The oxidizing agent is a substance having a sufficient redox potential to oxidize the surface of the object to be polished. For example, the oxidizing agent can be a substance having a redox potential higher than the redox potential of the object (material) to be polished at the pH at which polishing is performed. Here, the pH at which the polishing is performed is usually the same as the pH of the polishing composition. The redox potential of the object (material) to be polished is determined by dispersing the powder of the material in water to make a slurry, adjusting the pH of the slurry to the same as that of the polishing composition, and then measuring the redox potential of the slurry (the redox potential against the standard hydrogen electrode at a liquid temperature of 25°C) using a commercially available redox potentiometer.
[0065] In the polishing composition according to the present invention, the oxidizing agent is hydrogen peroxide. By using hydrogen peroxide, the polishing selectivity can be controlled in a polishing object containing two or more different film types. According to one embodiment, by using hydrogen peroxide, the titanium nitride film can be polished at a higher polishing rate than the polishing rate of the silicon oxide film.
[0066] The polishing composition of the present invention may contain an oxidizing agent other than hydrogen peroxide, but in order to better exhibit the effects of the present invention, it is preferable that the polishing composition does not contain an oxidizing agent other than hydrogen peroxide.
[0067] The content of the oxidizing agent in the polishing composition is suitably 0.001 mol / L (1 mM) or more. From the viewpoint of controlling the polishing selectivity in the polishing object containing two or more different film types (for example, from the viewpoint of improving the polishing rate of the titanium nitride film), in some embodiments, the content of the oxidizing agent is preferably 0.005 mol / L (5 mM) or more, more preferably 0.007 mol / L (7 mM) or more, even more preferably 0.01 mol / L (10 mM) or more, particularly preferably 0.015 mol / L (15 mM) or more, and most preferably 0.03 mol / L (30 mM) or more. From the viewpoint of controlling the polishing selectivity in a polishing object containing two or more different film types (e.g., from the viewpoint of improving the polishing selectivity of titanium nitride / silicon oxide), the content of the oxidizing agent is suitably 10 mol / L (10,000 mM) or less, preferably 5 mol / L (5,000 mM) or less, more preferably 3 mol / L (3,000 mM) or less (e.g., 2.5 mol / L (2,500 mM) or less, or 2 mol / L (2,000 mM) or less), even more preferably 1 mol / L (1,000 mM) or less, particularly preferably 0.5 mol / L (500 mM) or less, and most preferably 0.1 mol / L or less.
[0068] From the above, the content of the oxidizing agent in the polishing composition is suitably 0.001 mol / L or more and 10 mol / L or less, preferably 0.001 mol / L or more and 5 mol / L or less, more preferably 0.005 mol / L or more and 3 mol / L or less, even more preferably 0.007 mol / L or more and 1 mol / L or less, particularly preferably 0.01 mol / L or more and 0.5 mol / L or less, and most preferably 0.02 mol / L or more and 0.1 mol / L or less.
[0069] [pH] The pH of the polishing composition of the present invention is 2 or more and 4 or less, preferably 2.0 or more and 4.0 or less, more preferably more than 2 and less than 4, even more preferably 2.2 or more and 3.8 or less, and particularly preferably 2.5 or more and 3.5 or less. When the pH is within the above range, the desired effect of the present invention is more effectively exhibited.
[0070] The pH of the polishing composition can be measured specifically by the method described in the Examples.
[0071] The polishing composition of the present invention contains abrasive grains, abrasion inhibitor, organic acid, and oxidizing agent as essential components, but if it is difficult to obtain the desired pH using these alone, a pH adjuster may be added to adjust the pH within a range that does not impair the effects of the present invention.
[0072] The pH adjuster may be either an alkali or an acid other than the above organic acids (i.e., an inorganic acid). However, in order to further exert the effects of the present invention, it is preferable that the polishing composition of the present invention does not contain an inorganic acid. The pH adjuster may be used alone or in combination of two or more kinds.
[0073] Specific examples of inorganic acids used as pH adjusters include hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid, boric acid, carbonic acid, hypophosphorous acid, phosphorous acid, and phosphoric acid.
[0074] Examples of bases that can be used as pH adjusters include, for example, hydroxides or salts of Group 1 elements, hydroxides or salts of Group 2 elements, quaternary ammonium hydroxides or salts thereof, etc. Examples of salts include carbonates, bicarbonates, sulfates, acetates, etc.
[0075] The amount of the pH adjuster added is not particularly limited, and may be appropriately adjusted so that the polishing composition has a desired pH.
[0076] [Dispersion medium] The polishing composition according to the present invention preferably contains a dispersion medium for dispersing each component. Examples of the dispersion medium include water; alcohols such as methanol, ethanol, and ethylene glycol; ketones such as acetone, and mixtures thereof. Of these, water is preferable as the dispersion medium. That is, according to a preferred embodiment of the present invention, the dispersion medium contains water. According to a more preferred embodiment of the present invention, the dispersion medium is substantially composed of water. Note that the above-mentioned "substantially" means that a dispersion medium other than water may be included as long as the effects of the present invention can be achieved. More specifically, the dispersion medium is preferably composed of 90% by mass or more and 100% by mass or less of water and 0% by mass or more and 10% by mass or less of a dispersion medium other than water, and more preferably composed of 99% by mass or more and 100% by mass or less of water and 0% by mass or more and 1% by mass or less of a dispersion medium other than water. Most preferably, the dispersion medium is water.
[0077] From the viewpoint of not inhibiting the action of the components contained in the polishing composition, the dispersion medium is preferably water containing as few impurities as possible. Specifically, pure water or ultrapure water from which impurity ions are removed by ion exchange resin and then foreign matter is removed through a filter, or distilled water is more preferable.
[0078] [Electrical conductivity] In the present invention, the electrical conductivity of the polishing composition is preferably 0.05 mS / cm or more, more preferably 0.10 mS / cm or more, even more preferably 0.15 mS / cm or more, particularly preferably 0.18 mS / cm or more, and most preferably 0.20 mS / cm or more. By making the electrical conductivity of the polishing composition 0.05 mS / cm or more, the polishing selectivity of the object to be polished containing two or more different film types can be controlled. According to one embodiment, by making the electrical conductivity of the polishing composition 0.05 mS / cm or more, the contact between the abrasive grains and the object to be polished can be increased, and the titanium nitride film can be polished at a higher polishing rate, while the effect of suppressing the polishing rate of silicon oxide by the polishing suppressor can be maintained, and thus the polishing selectivity of titanium nitride / silicon oxide is improved. In the present invention, the electrical conductivity of the polishing composition is preferably 5.0 mS / cm or less, more preferably 2.0 mS / cm or less, even more preferably 1.0 mS / cm or less, particularly preferably 0.80 mS / cm or more, and most preferably 0.50 mS / cm or more. The electrical conductivity of the polishing composition may be 0.45 mS / cm or less, or may be 0.40 mS / cm or less. By having the electrical conductivity of the polishing composition be 5.0 mS / cm or less, the polishing selectivity can be controlled in a polishing object containing two or more different film types. According to one embodiment, in the present invention, by having the electrical conductivity of the polishing composition be 5.0 mS / cm or less, the contact between the abrasive grains and the polishing object can be sufficiently ensured, the effect of suppressing the polishing rate of silicon oxide by the polishing suppressor can be maintained, and the titanium nitride film can be polished at a high polishing rate.
[0079] In the present invention, the method for controlling the electrical conductivity of the polishing composition to a desired value is not particularly limited, but for example, it can be achieved by adding an electrical conductivity adjuster to the polishing composition. In the embodiment of the present invention, the electrical conductivity adjuster is not particularly limited as long as it can control the electrical conductivity to a desired value, but a salt compound is preferable.
[0080] [Other ingredients] The polishing composition according to the present invention may further contain known additives that can be used in polishing compositions, such as complexing agents, preservatives, fungicides, water-soluble polymers, and dissolution aids, within the range that does not inhibit the effects of the present invention. The polishing composition according to the present invention is acidic. For this reason, it is more preferable that the polishing composition contains a fungicide. That is, in one embodiment of the present invention, the polishing composition is substantially composed of at least one selected from the group consisting of abrasive grains, polishing inhibitors, dispersion mediums, organic acids, and oxidizing agents, as well as pH adjusters, dissolution aids, and fungicides. In one embodiment of the present invention, the polishing composition is substantially composed of at least one of abrasive grains, polishing inhibitors, dispersion mediums, organic acids, and oxidizing agents, as well as pH adjusters, dissolution aids, and fungicides. Here, "the polishing composition is substantially composed of abrasive grains, polishing suppressors, dispersion medium, organic acid, oxidizing agent, and at least one of pH adjuster, dissolution aid, and antifungal agent" means that the total content of the abrasive grains, polishing suppressors, dispersion medium, organic acid, oxidizing agent, pH adjuster, dissolution aid, and antifungal agent is more than 99 mass% (upper limit: 100 mass%) with respect to the polishing composition. Preferably, the polishing composition is composed of at least one of abrasive grains, polishing suppressors, dispersion medium, organic acid, oxidizing agent, pH adjuster, dissolution aid, and antifungal agent (the total content=100 mass%).
[0081] The antifungal agent (preservative) is not particularly limited and can be appropriately selected depending on the desired use and purpose.Specific examples include isothiazoline preservatives such as 1,2-benzoisothiazol-3(2H)-one (BIT), 2-methyl-4-isothiazolin-3-one, and 5-chloro-2-methyl-4-isothiazolin-3-one, and phenoxyethanol.
[0082] The dissolution aid is a substance that is present when the water-soluble polymer is dissolved in a dispersion medium (solvent) to improve the solubility of the water-soluble polymer. The polishing composition according to one embodiment of the present invention may further include a dissolution aid.
[0083] Examples of the dissolution aid include alcohol compounds such as methanol, ethanol, 1-propanol, 2-propanol, ethylene glycol, and propylene glycol; ether compounds such as diethylene glycol diethyl ether, 2-methoxyethanol, 2-ethoxyethanol, diethylene glycol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, triethylene glycol, triethylene glycol monomethyl ether, tetraethylene glycol, dipropylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, tripropylene glycol monomethyl ether, diacetone alcohol, 2-methoxyethyl acetate, 2-ethoxyethyl acetate, and diethylene glycol monoethyl ether acetate; and ketone compounds such as acetone, methyl ethyl ketone, acetylacetone, and cyclohexanone. These dissolution aids can be used alone or in combination of two or more.
[0084] [Polishing method and semiconductor substrate manufacturing method] The polishing composition of the present invention is preferably used for polishing an object to be polished that contains two or more different film types. According to one embodiment, the polishing composition of the present invention is preferably used for polishing an object to be polished that contains, for example, titanium nitride and silicon oxide. Thus, the present invention provides a polishing method comprising polishing an object to be polished with the polishing composition of the present invention. The present invention also provides a method for producing a semiconductor substrate comprising polishing a semiconductor substrate with the polishing composition of the present invention. The present invention also provides a method for producing a semiconductor substrate comprising polishing a semiconductor substrate by the polishing method of the present invention.
[0085] As a polishing device, a general polishing device can be used which is equipped with a holder for holding a substrate or the like having an object to be polished, a motor whose rotation speed can be changed, and a polishing platen onto which a polishing pad (polishing cloth) can be attached.
[0086] The polishing pad may be made of any material, including general nonwoven fabric, polyurethane, porous fluororesin, etc. It is preferable that the polishing pad has grooves formed thereon to allow the polishing liquid to accumulate.
[0087] Regarding the polishing conditions, for example, the rotation speed of the polishing platen and the carrier was 10 rpm (0.17 s -1 ) or more 500rpm (8.33s -1 The pressure (polishing pressure) applied to the substrate having the object to be polished is preferably 0.5 psi (3.4 kPa) or more and 10 psi (68.9 kPa).
[0088] The method of supplying the polishing composition to the polishing pad is not particularly limited, and for example, a method of continuously supplying the composition using a pump, etc. is adopted. There is no limit to the amount of the composition supplied, but it is preferable that the surface of the polishing pad is always covered with the polishing composition according to the present invention.
[0089] After polishing, the substrate is washed with running water, and water droplets adhering to the substrate are removed by a spin dryer or the like, followed by drying to obtain a substrate having a metal-containing layer.
[0090] The polishing composition of the present invention may be a one-liquid type or a multi-liquid type such as a two-liquid type. The polishing composition of the present invention may be prepared by diluting the stock solution of the polishing composition, for example, 3 times or more (or, for example, 5 times or more) with a diluting liquid such as water.
[0091] [Polishing selectivity of titanium nitride / silicon oxide] The polishing method according to the present invention can polish an object to be polished that contains silicon oxide and titanium nitride at a specific polishing rate ratio. The polishing method according to the present invention can be preferably applied to polishing (e.g., finish polishing) an object to be polished that contains silicon oxide and titanium nitride.
[0092] The lower limit of the polishing speed of titanium nitride is preferably more than 500 Å / min, more preferably 550 Å / min or more, even more preferably 600 Å / min or more, particularly preferably 650 Å / min or more, and most preferably 700 Å / min or more. By the polishing speed exceeding 500 Å / min, the polishing of titanium nitride proceeds favorably. The upper limit of the polishing speed of the titanium nitride film is not particularly limited, but in practical use, it is 8000 Å / min or less. Note that 1 Å=0.1 nm.
[0093] The upper limit of the polishing speed of silicon oxide is preferably 50 Å / min or less, more preferably 40 Å / min or less, and even more preferably 30 Å / min or less. By making the polishing speed 50 Å / min or less, the polishing selectivity of titanium nitride to silicon oxide can be further improved. The lower limit of the polishing speed of the silicon oxide film is not particularly limited, but is practically 5 Å / min or more. The polishing selectivity of titanium nitride to silicon oxide is preferably 15 or more, more preferably 17 or more, even more preferably 18 or more, and particularly preferably 20 or more.
[0094] Although the embodiments of the present invention have been described in detail, it is apparent that the same are illustrative and exemplary, not restrictive, and the scope of the present invention should be interpreted by the appended claims.
[0095] The present invention encompasses the following aspects and configurations.
[0096] 1. A polishing composition comprising an abrasive grain, an acid, a polishing inhibitor, and an oxidizing agent, wherein the abrasive grain has a positive zeta potential, the acid is an organic acid, the polishing inhibitor contains a nonionic surfactant, the oxidizing agent is hydrogen peroxide, and the polishing composition has a pH of 2 or more and 4 or less.
[0097] 2. The polishing composition according to 1 above, wherein the polishing inhibitor is a compound having a polyoxyalkylene glycol structure.
[0098] 3. The polishing composition according to 1 or 2 above, wherein the abrasive grains are cation-modified silica.
[0099] 4. The polishing composition according to any one of 1. to 3. above, wherein the polishing suppressor is polypropylene glycol having a number average molecular weight of 200 or more and less than 1,000.
[0100] 5. The polishing composition according to any one of 1. to 4. above, wherein the organic acid is 10-camphorsulfonic acid.
[0101] 6. The polishing composition according to any one of 1. to 5. above, wherein the content of the abrasive grains is 0.01 mass % or more and 3.0 mass % or less based on the total mass of the polishing composition.
[0102] 7. A polishing method comprising the step of polishing an object to be polished with the polishing composition according to any one of 1. to 6. above.
[0103] 8. A method for producing a semiconductor substrate, comprising the step of polishing a semiconductor substrate by the polishing method described in 7 above. EXAMPLES
[0104] The present invention will be described in more detail with reference to the following examples and comparative examples. However, the technical scope of the present invention is not limited to the following examples. In addition, unless otherwise specified, "%" and "parts" mean "% by mass" and "parts by mass", respectively.
[0105] <Average primary particle size of abrasive grains> The average primary particle size of the abrasive grains was calculated from the specific surface area of the silica particles measured by the BET method using "Flow Sorb II 2300" manufactured by Micromeritics, and the density of the abrasive grains.
[0106] <Average secondary particle size of abrasive grains> The average secondary particle diameter of the abrasive grains was measured as the volume average particle diameter (arithmetic mean diameter based on volume; Mv) using a dynamic light scattering particle size / particle size distribution analyzer UPA-UTI151 (manufactured by Nikkiso Co., Ltd.).
[0107] <Average degree of association of abrasive grains> The average degree of association of the abrasive grains was calculated by dividing the value of the average secondary particle size of the abrasive grains by the value of the average primary particle size of the abrasive grains.
[0108] <Zeta potential of abrasive grains> The zeta potential of the abrasive grains in the polishing composition was measured by subjecting the polishing composition to a Zetasizer Nano manufactured by Malvern Panalytical and measuring it using the laser Doppler method (electrophoretic light scattering measurement method) at a measurement temperature of 25°C, and calculating the zeta potential by analyzing the obtained data using the Smoluchowski formula.
[0109] <pH of polishing composition> The pH of the polishing composition was measured using a glass electrode type hydrogen ion concentration indicator (Model number: F-23, manufactured by Horiba, Ltd.) and three-point calibration was performed using standard buffer solutions (phthalate pH buffer solution, pH: 4.01 (25°C), neutral phosphate pH buffer solution, pH: 6.86 (25°C), carbonate pH buffer solution, pH: 10.01 (25°C)).The glass electrode was then placed in the polishing composition and the pH value was recorded after stabilization for at least 2 minutes.
[0110] <Electrical Conductivity of Polishing Composition> The electrical conductivity of each polishing composition after preparation was measured using a tabletop electrical conductivity meter (manufactured by Horiba, Ltd., model number: DS-71).
[0111] <Measurement of number average molecular weight (Mn) of nonionic surfactants> The number average molecular weight (Mn) of the nonionic surfactant was determined by gel permeation chromatography (GPC) using the number average molecular weight (converted into polyethylene glycol). The number average molecular weight was measured using the following apparatus and conditions: GPC equipment: Shimadzu Corporation Model: Prominence + ELSD detector (ELSD-LTII) Column: VP-ODS (Shimadzu Corporation) Mobile phase A: Methanol B: 1% acetic acid solution Flow rate: 1mL / min Detector: ELSD temp. 40℃, Gain 8, N2GAS 350kPa Oven temperature: 40℃ Injection volume: 40μL.
[0112] [Preparation of polishing composition] Example 1 In the same manner as in Example 1 of JP 2005-162533 A, γ-aminopropyltriethoxysilane (APTES) was used as a silane coupling agent at a concentration of 0.32 mmol (0.32 mM) per 1 L of an aqueous dispersion of silica sol (silica concentration=20% by mass), to prepare a cocoon-shaped cation-modified colloidal silica having an average primary particle size of 25.0 nm, an average secondary particle size of 50.0 nm, an average degree of association of 2.0, and an aspect ratio of 1.2.
[0113] The cation-modified colloidal silica obtained above was added as an abrasive grain to pure water as a dispersion medium at room temperature (25° C.) so as to have a final concentration of 1.8% by mass. Furthermore, 2-methyl-4-isothiazolin-3-one (manufactured by The Dow Chemical Company) was added as an antifungal agent to have a final concentration of 0.013 mM to obtain a mixed solution.
[0114] Thereafter, polypropylene glycol (Mw: 400, manufactured by Sanyo Chemical Industries, Ltd.) (shown as "PPG400" in the table) was added as a surfactant to a final concentration of 0.1 mass%, and 10-camphorsulfonic acid (shown as "CSA" in the table) was added as an organic acid to a pH of 3.1, and the mixture was stirred and mixed at room temperature (25°C) for 30 minutes, and a 31 mass% aqueous hydrogen peroxide solution (manufactured by Santoku Chemical Industries Co., Ltd.) was added as an oxidizing agent to a predetermined content (mM) shown in Table 1 to prepare a polishing composition. The pH of the resulting mixture was measured to be 3.1, and the electrical conductivity was 0.43 mS / cm.
[0115] The zeta potential of the cation-modified colloidal silica in the obtained polishing composition was measured according to the above-mentioned method, and was found to be +22.8 mV. Furthermore, the particle size of the cation-modified colloidal silica in the polishing composition was the same as that of the cation-modified colloidal silica used.
[0116] (Examples 2 to 9, Comparative Examples 1 to 5) Each polishing composition was prepared in the same manner as in Example 1, except that the type and concentration of each component, as well as the pH, were changed as shown in Table 1 below. The composition of each polishing composition is shown in Table 1 below. The polishing compositions of Examples 4 and 5 and Comparative Example 5 had an abrasive concentration of 0.9 mass%. The pH of each polishing composition was measured, and the values shown in Table 1 were obtained. In Table 1 below, "PPG1000" indicates polypropylene glycol (Mw: 1000), "PEG400" indicates polyethylene glycol (Mw: 400), "PEG lauryl ether" indicates polyethylene glycol lauryl ether (Mw: 400), and "-" indicates that the agent was not used.
[0117] The particle size of the cation-modified colloidal silica in the polishing compositions of Examples 2 to 9 and Comparative Examples 1 to 5 was similar to the particle size of the cation-modified colloidal silica used.
[0118] <Evaluation of Polishing Rate of Polishing Composition> Using each of the polishing compositions prepared above, the surface of the object to be polished was polished under the following conditions: The objects to be polished were a silicon wafer (300 mm, blanket wafer) with a titanium nitride (TiN) film of 2500 Å thickness formed on its surface, and a silicon wafer (300 mm, blanket wafer) with a TEOS type silicon oxide (SiO2) film (hereinafter, "TEOS film") of 10000 Å thickness formed on its surface.
[0119] (Polishing equipment and polishing conditions) Polishing equipment: Ebara Corporation polishing machine (model FREX 300E) Polishing pad: Nitta DuPont Polyurethane Pad IC1000 Polishing pressure: 3.0 psi (1 psi = 6894.76 Pa) Polishing platen rotation speed: 113 rpm Supply of polishing composition: free-flowing Polishing composition supply amount: 250ml / min Polishing time: 1 minute.
[0120] (Evaluation of polishing speed) The thickness of the titanium nitride film before and after polishing was measured using a sheet resistance meter (VR120 / 08SD: manufactured by Kokusai Electric Semiconductor Services Co., Ltd.) based on the DC four-point probe method. The thickness of the TEOS film before and after polishing was measured using an optical film thickness meter (ASET-f5x: manufactured by KLA-Tencor Corporation). The polishing speed for each object was calculated from the measured thickness by dividing [(thickness before polishing) - (thickness after polishing)] by the polishing time. For titanium nitride films, if the polishing speed exceeds 500 Å / min, it is practical. For TEOS films, if it is 50 Å / min or less, it is practical.
[0121] The above evaluation results are also shown in Table 1. In Tables 1 and 2, the titanium nitride film is indicated as "TiN" and the TEOS film is indicated as "SiO2".
[0122] [Table 1]
[0123] As is clear from Table 1 above, when the polishing composition of the Example was used, it was found that the polishing rate of the silicon oxide (SiO2) film was suppressed while the titanium nitride (TiN) film was polished at a high polishing rate, and a high polishing selectivity was shown. On the other hand, the polishing composition of the Comparative Example tended to increase the polishing rate of the silicon oxide film.
[0124] Therefore, it is understood that the polishing composition of the present invention can polish a titanium nitride film at a higher polishing rate than the polishing rate for a silicon oxide film.
Claims
1. A polishing composition comprising an abrasive, an acid, a polishing inhibitor, and an oxidizing agent, The abrasive grains have a positive zeta potential; the acid is an organic acid, The polishing inhibitor contains a nonionic surfactant, the oxidizing agent is hydrogen peroxide; A polishing composition having a pH of 2 or more and 4 or less.
2. The polishing composition according to claim 1 , wherein the polishing inhibitor is a compound having a polyoxyalkylene glycol structure.
3. The polishing composition according to claim 1 or 2, wherein the abrasive grains are cation-modified silica.
4. 3. The polishing composition according to claim 1, wherein the polishing inhibitor is a polypropylene glycol having a number average molecular weight of 200 or more and less than 1,000.
5. 3. The polishing composition according to claim 1, wherein the organic acid is 10-camphorsulfonic acid.
6. 3. The polishing composition according to claim 1, wherein the content of the abrasive grains is 0.01 mass % or more and 3.0 mass % or less based on the total mass of the polishing composition.
7. A polishing method comprising a step of polishing an object to be polished with the polishing composition according to claim 1.
8. A method for producing a semiconductor substrate, comprising the step of polishing a semiconductor substrate by the polishing method according to claim 7.
Citation Information
Patent Citations
Chemical / Mechanical polishing slurry useful for copper substrate
JP1999021546A